Strategi Pemasaran Virtual Influencer di Indonesia: Analisis Persepsi Konsumen Gen Z terhadap Karakter Digital - Riu, Isma Azis (PT Maju Malaqbi Makkarana, 2025)
This study examines the marketing strategies of virtual influencers in Indonesia, focusing on Generation Z’s perceptions in Jakarta. Using a qualitative phenomenological approach (in-depth interviews and FGDs with 25 participants), the research reveals consumer ambivalence: while virtual influencers like Kyra and Thalasya AI attract through futuristic aesthetics and local cultural integration, skepticism about authenticity and ethical concerns over deepfake risks persist. Findings indicate that Generation Z prefers human influencers for personal-value products but appreciates virtual influencers in image-driven categories (fashion/technology). Practical implications emphasize the need for content transparency (AI-generated labels) and glocal strategies that blend technology with socio-religious values. The study recommends ethical regulations to balance digital marketing innovation with consumer protection.